1989
DOI: 10.1159/000118610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment with Various Doses of Haloperidol on the Pituitary-Gonadal Axis in Male Schizophrenic Patients

Abstract: Fifteen male paranoid schizophrenics underwent an initial 4-week therapy with haloperidol 7.5 mg/day, and a subsequent 4-week treatment with haloperidol 15 mg/day, p.o. (group I). Another 15 male paranoid schizophrenics received an initial 4-week treatment with haloperidol 30 mg/day, and a subsequent 4-week therapy with haloperidol 60 mg/day, p.o. (group II). In each group of patients, serum prolactin (PRL), luteinizing hormone (LH) and testosterone (T) levels were measured before treatment and at the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…35 Other suggested mechanisms are the lowering of testosterone levels in response to prolactin elevations. 36 We could not find a correlation between prolactin and testosterone levels.…”
Section: Discussionmentioning
confidence: 59%
“…35 Other suggested mechanisms are the lowering of testosterone levels in response to prolactin elevations. 36 We could not find a correlation between prolactin and testosterone levels.…”
Section: Discussionmentioning
confidence: 59%
“…Most studies on patients taking the usual clinical doses showed little or no effect of treatment with haloperidol, pimozide or penfluridol on luteinizing hormone (LH) and testosterone (Brambilla et al 1975;Nathan et al 1980;Siris et al 1980). A reduction in plasma testosterone but not LH was reported only in patients on high (30-60 mg daily) haloperidol doses (Rinieris et al 1989), while a reduction in LH and testosterone has been repeatedly found during treatment with thioridazine (Laughren et al 1978;Brown et al 1981). …”
Section: Introductionmentioning
confidence: 97%
“…Overall there was no significant difference in testosterone concentrations between users and non-users of psychiatric medications. There is limited evidence that men taking commonly used psychiatric medications have lower testosterone 19 , 20 , 2232. In our review, we found that 31.3% and 25% of the men using any psychiatric medication were in the lowest quartile of total and free testosterone, respectively; however, the relationships between total or free testosterone and degree of hypogonadism failed to reach statistical significance.…”
Section: Discussionmentioning
confidence: 60%